Dopamine transporter occupancy by methylphenidate and impulsivity in adult ADHD. (June 2014) - Crunelle, Cleo L.; van den Brink, Wim; Dom, Geert; Booij, Jan
Summary: Impulsivity is a multidimensional construct, including impulsive decision-making and impulsive action, representing relatively independent neurocircuitries. ADHD is treated with methylphenidate, a drug that binds to dopamine transporters. This study in 24 adult male patients with ADHD shows that dopamine transporter occupancy by methylphenidate in the putamen correlates with improvements in cognitive but not in motor impulsivity.